Primary cellulitis and cutaneous abscess caused by Yersinia enterocolitica in an immunocompetent host: A case report and literature review. Issue 26 (June 2016) - Kato, Hirofumi; Sasaki, Shugo; Sekiya, Noritaka
Abstract : Abstract: Primary extraintestinal complications caused by Yersinia enterocolitica are extremely rare, especially in the form of skin and soft-tissue manifestations, and little is known about their clinical characteristics and treatments. We presented our case and reviewed past cases of primary skin and soft-tissue infections caused by Y enterocolitica . We report a case of primary cellulitis and cutaneous abscess caused by Y enterocolitica in an immunocompetent 70-year-old woman with keratodermia tylodes palmaris progressiva. She presented to an outpatient clinic with redness, swelling, and pain of the left ring finger and left upper arm without fever or gastrointestinal symptoms 3 days before admission. One day later, ulceration of the skin with exposed bone of the proximal interphalangeal joint of the left ring finger developed, and cefditoren pivoxil was described. However, she was admitted to our hospital due to deterioration of symptoms involving the left finger and upper arm. Cefazolin was initiated on admission, then changed to sulbactam/ampicillin and vancomycin with debridement of the left ring finger and drainage of the left upper arm abscess. Wound culture grew Y enterocolitica serotype O:8 and methicillin-sensitive Staphylococcus aureus . Blood cultures were negative and osteomyelitis was ruled out. Vancomycin was switched to ciprofloxacin, then skin and soft-tissue manifestations showed clear improvement within a few days. The patient received 14 days of ciprofloxacin and oral amoxicillin/clavulanate and has since shown no recurrence. We reviewed 12 cases of primary skin and soft-tissue infections caused by Y enterocolitica from the literature. In several past cases, portal entry involved failure of the skin barrier on distal body parts. Thereafter, infection might have spread to the regional lymph nodes from the ruptured skin. Y enterocolitica is typically resistant to aminopenicillins and narrow-spectrum cephalosporins. In most cases, these inefficient antibiotic agents were initially prescribed, but patient conditions rapidly improved after implementing appropriate therapy and drainage. In addition, primary skin and soft-tissue infections occurred even in patients lacking risk factors. Physicians should consider the rare differential diagnosis of Y enterocolitica infection when seeing patients with deteriorating skin lesions under standard treatment, even if the patient is immunocompetent.